Endurance training and testing with the ball in young elite soccer players - Chamari, K.; Hachana, Y; Kaouech, F.; Jeddi, R; Moussa-Chamari, I.; Wisløff, U. (British Journal of Sports Medicine, 2005)
Background: The aerobic capacity of soccer players substantially influences their technical performance and tactical choices. Thus, the assessment of soccer players` aerobic performance should be of interest for soccer coaches in order to evaluate and improve their endurance training sessions. In this study, we present a new test to assess aerobic performance in soccer by means of a specific dribbling track: the Hoff test. We further determined whether improvement in maximal oxygen uptake was reflected in increased distance covered in the Hoff test.